The Future of Virtual Reality in Mental Health Care: Toward Remote, AI-Driven Therapy - Sudeep Chakraborthy F; J. Gokulapriya (Journal of Computer Based Parallel Programming, 2025)
The global rise in mental health challenges, especially in the post-pandemic era, highlights the urgent need for innovative therapy solutions. This paper explores the transformative potential of Virtual Reality (VR) integrated with Artificial Intelligence (AI) in revolutionizing mental health care. By creating immersive environments tailored to individual needs, AI-VR therapy systems offer remote, personalized, and data-driven mental health interventions. The study discusses current trends, system architecture, and the implementation of AI-driven VR modules that support therapies for conditions like PTSD, anxiety, and depression. It also emphasizes privacy, therapist involvement, and ethical use of data. The convergence of VR and AI paves the way for more engaging, accessible, and scalable mental health care. This paper outlines future directions and implications for clinical practice, with a focus on improving therapeutic outcomes while addressing systemic healthcare challenges.